Optimize Retail System Performance by Analyzing Big Data and Visualizing with Power BI - Quoc, Huu Dang; Thi, Hue Man; Thi Ngoc, Mai Nguyen; Dieu, Huong Vu (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Digital transformation significantly improves business performance and customer experience and adapts to the pace of change in the business environment. Applying digital transformation technologies to business causes the retail industry to gain data very quickly, creating a big data system requiring the ability to perform extensive data analysis and management. Businesses can improve their operational capacity and competitiveness by discovering the data source better. The article presents the method of designing and organizing data and the relationship of data objects in a data warehouse system. Data in the warehouse will be synthesized using computational algorithms to extract useful information and then visualized using data analysis tools, representing data with the output in the reporting charts. They help turn digital data into easy-to-understand visuals, helping retailers see patterns, trends and essential information. Businesses can achieve many meaningful benefits, such as improving operational performance, increasing revenue, predicting trends, etc... by using many charts. Data representation into understandable information is accomplished with the intelligent analysis tool Microsoft PowerBI.